2023
DOI: 10.2147/ndt.s393773
|View full text |Cite
|
Sign up to set email alerts
|

Jiedu Yizhi Formula Improves Cognitive Function by Regulating the Gut Dysbiosis and TLR4/NF-κB Signaling Pathway

Abstract: Objective The objective of this study was to explore the neuroprotective mechanism of JDYZF in treating AD from the perspective of inflammation and intestinal microflora. Methods A total of 24 APP/PS1 mice were randomly divided into four groups: model (n = 6), JDYZF low-dose (n = 6), JDYZF high-dose (n = 6), and positive drug (n = 6), six C57 mice were used as the control group. The body weights and diets of all mice were examined daily. After 8 weeks of administration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…In a pig model, CM could modulate the intestinal barrier function by improving intestinal morphology, elevating the expression of zona occluden-1, claudin-1, down-regulating pro-inflammatory cytokines and up-regulating anti-inflammatory cytokines due to its effect on suppressing the expression of key proteins of the TLR4/NF-κB signaling pathway. It also changed the gut microbial composition and increased the levels of acetate and butyrate ( Zhang P. et al, 2023 ). The modulatory effects of cordycepin on gut microbiota and metabolites may be one of the specific mechanisms influencing AD progression, which still needs to be further confirmed.…”
Section: Herbal Medicine and Admentioning
confidence: 99%
“…In a pig model, CM could modulate the intestinal barrier function by improving intestinal morphology, elevating the expression of zona occluden-1, claudin-1, down-regulating pro-inflammatory cytokines and up-regulating anti-inflammatory cytokines due to its effect on suppressing the expression of key proteins of the TLR4/NF-κB signaling pathway. It also changed the gut microbial composition and increased the levels of acetate and butyrate ( Zhang P. et al, 2023 ). The modulatory effects of cordycepin on gut microbiota and metabolites may be one of the specific mechanisms influencing AD progression, which still needs to be further confirmed.…”
Section: Herbal Medicine and Admentioning
confidence: 99%
“…There is great concern about the clinical relevance of studying the intestinal microbiota in patients with AD. Some studies showed that changes in intestinal microbial composition were associated with cognition, especially memory [108,109], while others collected important clinical characteristics, such as educational level, APOE genetic background, cognitive function, and illness severity. The occurrence of the genera Saccharimonadales, Patescibacteria and Saccharimonadia was found to be related to aging.…”
Section: The Role Of Apoe and Apoe Mimetic Peptides On The Intestinal...mentioning
confidence: 99%
“…JDYZF is composed of seven traditional Chinese medicines, which were obtained from the same source and were subjected to rigorous quality control measures. It has been demonstrated that JDYZF exerts an impact on the brains of APP/PS1 transgenic mice by reducing the neuroin ammatory response and decreasing the deposition of Aβ through the regulation of the brain TLR4/NF-κB pathway (Zhang et al 2023). The group conducted an experiment where they extracted polysaccharides from Coptis chinensis Franch(CCF), the primary drug in the formula under investigation.…”
Section: Introductionmentioning
confidence: 99%